2019
DOI: 10.1136/jech-2019-213162
|View full text |Cite
|
Sign up to set email alerts
|

Persisting inequalities in birth outcomes related to neighbourhood deprivation

Abstract: IntroductionHealth inequalities can be observed in early life as unfavourable birth outcomes. Evidence indicates that neighbourhood socioeconomic circumstances influence health. However, studies looking into temporal trends in inequalities in birth outcomes including neighbourhood socioeconomic conditions are scarce. The aim of this work was to study how inequalities in three different key birth outcomes have changed over time across different strata of neighbourhood deprivation.MethodsNationwide time trends e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
29
0
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 27 publications
(31 citation statements)
references
References 34 publications
0
29
0
1
Order By: Relevance
“…Given that some experts favour monitoring absolute inequality for public health planning, management and evaluation,7 8 and that declines in relative inequality seem conceivable under far fewer conditions in Western European countries,9 it is tempting to conclude from the overall findings that deprivation-related perinatal inequalities have generally improved in the Netherlands. While absolute rates of birth outcomes decreased across all areas ranging from least (top quintile) to most (bottom quintile) deprived, the largest improvements were observed in the most deprived quintile 4…”
mentioning
confidence: 92%
See 4 more Smart Citations
“…Given that some experts favour monitoring absolute inequality for public health planning, management and evaluation,7 8 and that declines in relative inequality seem conceivable under far fewer conditions in Western European countries,9 it is tempting to conclude from the overall findings that deprivation-related perinatal inequalities have generally improved in the Netherlands. While absolute rates of birth outcomes decreased across all areas ranging from least (top quintile) to most (bottom quintile) deprived, the largest improvements were observed in the most deprived quintile 4…”
mentioning
confidence: 92%
“…A robust literature has found that babies who are born to mothers living in areas of higher deprivation have an increased risk of adverse birth outcomes, such as prematurity and restricted fetal growth 3. Given that these suboptimal outcomes lead to poorer developmental trajectories in childhood4 and chronic diseases in later adulthood,5 health at birth is a profoundly important priority for public health and social care. Despite substantial improvements in perinatal morbidity and mortality over time in Europe as a whole, advances have been slower in the Netherlands 4…”
mentioning
confidence: 99%
See 3 more Smart Citations